Utilization of plastic waste as a planting medium for microgreens to meet the families' nutritional needs during the pandemic - Yayat Sujatna; Widi Hastomo; Ambardi Ambardi (Universitas Muhammadiyah Magelang, 2022)
Plastics are used for various purposes and are an important part of everyday life. People use a lot of bags, bottles, utensils, furniture made of plastic and many other household items without considering the fact that it will create a lot of waste that is impossible to manage. In order to meet their daily nutritional needs during the pandemic, urban communities can take advantage of urban farming microgreens by utilizing plastic waste as a planting medium. Microgreens are a category of super food that are rich in nutrients, vitamins and minerals, fast harvesting times and easy planting, making them the right choice for urban communities. Based on this explanation, the Community Service program carried out at PCM Cengkareng Barat, aims to educate residents about plastic waste, recycle plastic waste to be used as microgreens planting media and invites urban farming microgreens to meet family nutrition independently during the Covid-19 pandemic. This program uses the Participatory Rural Appraisal (PRA) method to provide solutions to partners. The result of this program is the increased ability and knowledge of partners about the use of plastic waste, as well as new methods of urban farming microgreens.